Women's Religious Empowerment in Pesantren: Developing the Institutional Religious Empowerment Cycle - Ngadhimah, Mambaul; Muslim, Abu; Mujahada, Kharis Syuhud; Marpuah, Siti (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
Women's participation in Islamic da'wah has expanded significantly, yet the institutional mechanisms through which religious authority and empowerment are socially constructed remain insufficiently explained. This study examined how women's religious empowerment was developed within the Jamaah Santri Putri (JAMMSANTRI) community at Pondok Pesantren Hudatul Muna Jenes, Indonesia, by analysing the social construction of religious agency and identity. A qualitative case study was conducted using in-depth interviews, participant observation, and document analysis, with Berger and Luckmann's theory of the social construction of reality serving as the analytical framework. The findings revealed that women's empowerment evolved through four interconnected processes: collective religious participation, institutional reinforcement, identity reconstruction, and social reproduction that generated wider community transformation. Rather than functioning as isolated stages, these processes formed a recursive institutional cycle in which organizational participation continuously reinforced religious identity, leadership, and community engagement. The study further refined Berger and Luckmann's framework by demonstrating that religious institutions actively mediated and reproduced women's religious agency through structured programmes, participatory leadership, and recurring organizational practices. It consequently proposed the Institutional Religious Empowerment Cycle (IREC) as a process-oriented model explaining how pesantren-based women's organizations simultaneously preserve religious traditions and generate sustainable social transformation.